Social media communication management in the media sector - Brigas, Joaquim; Gonçalves, Fátima; Gonçalves, Jorge (Revista Venezolana de Gerencia, 2023)
The production, distribution, and consumption of news have undergone fundamental changes, with social media providing an essential point of access to information. On these digital platforms, visual content has become increasingly important for the media sector. Nowadays, social media are a bridge for obtaining information, particularly on Instagram reels. The objective of this study was to investigate how news organisations make visual information available to the public, in particular the way in which reels are being used on social media. The profiles of three Portuguese national newspapers on the Instagram social network are analysed using a quantitative and qualitative approach. The variation of followers, the differences and similarities in the strategies used to distribute reels and how short videos are included to engage the target audience are analysed over the period. The way in which different journalistic genres are integrated into social media for the distribution of news is also presented, relating it to changes in communication management with the use of reels. The findings of this study suggest that social networks’ influence on journalistic management and practices is changing digital journalism.